Out of many : (Prentice-Hall, 1997)
Focusing on the rich cultural and ethnic diversity which characterizes the heritage of the USA, this book covers the complex interaction of social, political and historical forces which have shaped America and its people. The book intertwines the separate experiences and perceptions of diverse Americans - women and men, Native Americans, African Americans and European Americans, politicians and constituents - with an explanation of how differences of caste and class have been managed through established social and political channels, or have shaped the social fabric through accommodation, conflict or rebellion. This study also considers the roles of minority peoples in American history, including African Americans, Mexican Americans, Asians and Pacific Islanders. It covers pre-colonial slavery and empire in the colonial period, surveys the civil rights movement from the 1940s to the 1960s, and also provides full coverage of the post-1970 era.